2013
DOI: 10.1002/pc.22747
|View full text |Cite
|
Sign up to set email alerts
|

Novel composite biopolymers of sodium alginate/natural rubber/coconut waste for adsorption of Pb(II) ions

Abstract: A novel composite adsorbent in the form of beads for removal of Pb 21 from wastewater was prepared by blending a sodium alginate (NaAlg) solution, natural rubber (NR) latex, and coconut waste (cofiber). After being crosslinked by calcium chloride, the beads were highly stable, flexible, and easily used in the environment. The optimum composition of the beads with an average size of 1.1-1.2 mm was 4% NaAlg:NR latex (60% dry rubber content):cofiber at 50:1:0.72 and a 2%w/w CaCl 2 solution used for cross linking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This ionic crosslinking can improve the structural stability of the composite films and reinforce filler–filler and filler–rubber interactions, resulting in enhancement of the tensile strength of the composite film. After crosslinking sodium alginate/natural rubber/coconut composite by CaCl 2 , the composites were highly stable [ 35 ]. However, it was found that the mechanical properties of NR–BC films were reduced by crosslinking the composites by CaCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This ionic crosslinking can improve the structural stability of the composite films and reinforce filler–filler and filler–rubber interactions, resulting in enhancement of the tensile strength of the composite film. After crosslinking sodium alginate/natural rubber/coconut composite by CaCl 2 , the composites were highly stable [ 35 ]. However, it was found that the mechanical properties of NR–BC films were reduced by crosslinking the composites by CaCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Double network polymers with special interpenetrating network three-dimensional structure have widely attracted great attention in many fields, especially in the field of heavy metals adsorption, which has a good prospect of environmental application. [1][2][3] Heavy metals are common pollutants found in various industrial effluents, which have represented a serious threat to the environment and the human being because of their toxic and lethal effects, and adsorption technique is a promising method that is very important to remove the refractory pollutants from solution system because of its facile operation processes and high efficiency. Therefore, efficient adsorbents become the decisive factor in the adsorption process of heavy metals ions, and the researches on exploring the novel adsorbents with high efficiency for heavy metals adsorption become very essential.…”
Section: Introductionmentioning
confidence: 99%
“…The cofiber increased the porosity and contact. The adsorption efficiency of the composite beads was up to 99.6% of the Pb 2+ [41].…”
Section: Alginatementioning
confidence: 95%
“…After crosslinking sodium alginate/natural rubber/coconut composite by CaCl2, the composites were highly stable [41]. However, it was found that the mechanical Sulfur vulcanization generally changes the physical properties of natural rubbers.…”
Section: Mechanical Propertiesmentioning
confidence: 99%